1996
DOI: 10.1037/0022-006x.64.1.202
|View full text |Cite
|
Sign up to set email alerts
|

Telephone counseling for smoking cessation: Effects of single-session and multiple-session interventions.

Abstract: Smokers (N = 3,030) were randomized to receive 1 of 3 interventions: (a) a self-help quit kit, (b) a quit kit plus 1 telephone counseling session, or (c) a quit kit plus up to 6 telephone counseling sessions, scheduled according to relapse probability. Both counseling groups achieved significantly higher abstinence rates than the self-help group. The rates for having quit for at least 12 months by intention to treat were 5.4% for self-help, 7.5% for single counseling, and 9.9% for multiple counseling. The 12-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
238
0
11

Year Published

2002
2002
2011
2011

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 303 publications
(261 citation statements)
references
References 22 publications
9
238
0
11
Order By: Relevance
“…28,29 There seems to be a dose response effect, with multiple calls producing higher abstinence relative to a single call. 22 Promising results have been found for a small number of studies using telephone counseling to extend effects of a school-based prevention program, 30 to promote requitting among smokers with recent unsuccessful quit attempts, 31 to support short-term abstinence among low-income women provided with free nicotine patches and proactive calls, 32 to promote short-term abstinence among smokeless tobacco users, 33 and as part of a tailored intervention for African American smokers. 34 Mixed results have been found for proactive calls to augment personalized written feedback, with a 12-month effect found for calls when combined with stage-tailored materials and expert system personalized feedback in the second of 2 trials by Prochaska et al 35,36 and higher short-term abstinence reported in a trial by Curry et al 37 Mixed results have also been found for proactive calls to support nicotine replacement use.…”
Section: Evidence Base: Proactive Telecounselingmentioning
confidence: 99%
See 1 more Smart Citation
“…28,29 There seems to be a dose response effect, with multiple calls producing higher abstinence relative to a single call. 22 Promising results have been found for a small number of studies using telephone counseling to extend effects of a school-based prevention program, 30 to promote requitting among smokers with recent unsuccessful quit attempts, 31 to support short-term abstinence among low-income women provided with free nicotine patches and proactive calls, 32 to promote short-term abstinence among smokeless tobacco users, 33 and as part of a tailored intervention for African American smokers. 34 Mixed results have been found for proactive calls to augment personalized written feedback, with a 12-month effect found for calls when combined with stage-tailored materials and expert system personalized feedback in the second of 2 trials by Prochaska et al 35,36 and higher short-term abstinence reported in a trial by Curry et al 37 Mixed results have also been found for proactive calls to support nicotine replacement use.…”
Section: Evidence Base: Proactive Telecounselingmentioning
confidence: 99%
“…20 Variability has been found in results for individual applications of proactive calls. Efficacy has been demonstrated when proactive telecounseling is used as the primary intervention [21][22][23][24][25] and to augment hospital initiated interventions for cardiac patients 26,27 or general hospitalized patients. 28,29 There seems to be a dose response effect, with multiple calls producing higher abstinence relative to a single call.…”
Section: Evidence Base: Proactive Telecounselingmentioning
confidence: 99%
“…Five studies found that the TMH interventions used were successful, with use of telemedicine providing better outcomes than alternative approaches. [72][73][74][75][76] In the remaining study, the telemedicine intervention was unsuccessful, possibly associated with the approach taken to counselling. 77…”
Section: Alcohol and Substance Abusementioning
confidence: 99%
“…MI was chosen for its early promise in reducing adult smoking (Zhu et al, 1996;Britt et al, 1994;Curry et al, 1995), and its nonjudgmental, nonprescriptive style is appropriate for adolescent smokers (Lawendowski, 1998).…”
Section: Intervention Designmentioning
confidence: 99%